Teacher Professionalism In The Modern Era: A Study Of Professional Requirements And Code Of Ethics - Utami, Rani Mega; Fernando, Fernando; Ulya, Ratu Triana; Abdurrahmansyah, Abdurrahmansyah (International Journal of Education, Information Technology, and Others, 2026)
Teacher professionalism is a main pillar in ensuring the quality of education in the dynamic modern era. This research aims to analyze the concept of teacher professionalism by focusing on the fulfillment of professional requirements and the implementation of code of ethics amidst digital transformation. The method used is qualitative with a literature study approach (library research), which examines various scientific literatures, educational policies, and relevant research results. The results of the discussion show that teacher professionalism in the modern era is not only based on the mastery of four basic competencies (pedagogical, professional, personality, and social), but also requires adaptability to information technology and digital literacy. The main challenges found include the digital gap and the risk of dehumanizing interactions, while strengthening the code of ethics is a crucial instrument for maintaining the moral integrity of educators. This research concludes that efforts to strengthen professionalism must be carried out through continuous professional development and systematic institutional support to produce teachers who are able to balance technological skills with human values.